THE IMAGE OF THE SPIRITUAL WORLD OF THE HERO IN THE STORY "SHUM BOLA" BY G. GULAM (Scientific journal of the Fergana State University, 2024)
This article examines the prose heritage of academician G. Ghulam. In it, the originality of G. Ghulam's prose is studied on the example of the writer's short story "Shum Bola". G. Ghulam's ability to illuminate the hero‘s spiritual experiences is analyzed based on examples from the story. The researcher substantiates that the high human feelings of a number of characters in the work, such as Shum bola, Amon, Kazakh old woman, Aisha yallachi, Latifaxon, are depicted according to life logic. In this article, it is argued that the turmoil in the country and material shortages did not overshadow the high human qualities in the hearts of these heroes. The opinions expressed in the article are briefly summarized by the researcher.